A Glimpse into the Lives of Transferring Private School Students to a State College - Gabana, Jona J.; Madrigal, Dennis (Technium Social Sciences Journal, 2021)
Private schools ensure students' future with rigorous academic curricula that incorporate durable skills like pro-activeness, critical thinking, and collaboration. However, due to financial constraints, learners are left with no option but to enroll in a tertiary school that offers free of charge. Hence, this paper aims to inquire into the lives of transferring students from a private school to a state college. The researcher utilized the purposive sampling technique to determine the five participants of the study who were selected using inclusion criteria. Through qualitative research design, the data were gathered from the participants using an in-depth interview. Data were analyzed using a recursive textual analysis aided by Litchman's 3 C's-coding, categorizing, and conceptualizing. The findings reveal that participants shared usual experiences and observations in a state college. Notwithstanding the hardships to accomplish the desired purpose, the students remained focused and motivated. Thus, state college is a conducive avenue for a determined student to earn a degree and become successful in their chosen field.